Effect of Boron foliar spray on biochemical changes in Santa Teriza Lime Influence on Citrus Leaf Miner Damage. (Latakia University Journal -Biological Sciences Series, 2023)
The effect of foliar spray of  young lemon trees (santa teriza) with boric acid (500- 1000 ppm), on antioxidant enzymes activities (peroxidas POD, poly phenol oxidase PPO ), total phenolic content,  total chlorophyll and their influence on leaf miner (  Phyllocnistis   citrella) activity (  tunnel length and damage density  )  under field condition was investigated .The results showed that  boron 1000 ppm enhanced POD activity (0.387 mm-l mg -l protein) and PPO activity (1.389 ΔA/min/g FW), and decreased total phenolic content (4.622 mg/g). Both boron concentration improved total leaf chlorophyll content ( spad29.07- 24.06).  The results demonstrated as well that Boron treatment has a beneficial effect in reducing leaf miner activity, by decreasing  tunnel length and damage density.Key words: Boron- Santa teriza lime- Antioxidant enzymes- Total phenolic content_ Total chlorophyll-  Citrus leaf miner- Tunnel length- Damage density.